2020
DOI: 10.3390/pr8121658
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effects of Physical Properties of Tenera Palm Kernel during Drying and Its Moisture Sorption Isotherms

Abstract: A study on the effect of the physical properties and moisture sorption isotherm of palm kernels constitutes the critical criteria in evaluating the drying performance. The drying was evaluated as a function of moisture content (MC) in the range of 0.31–0.02 kg/kg (d.b.). Whereas, the equilibrium moisture content (EMC) of palm kernels (whole kernel and ground kernel) was determined experimentally using the standard gravimetric method at different temperatures (50 °C to 80 °C), over a range of relative humidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The highest value of 0.605% at 32.5% (db) mc presents that the seed is oval. Habibiasr et al (2020) likewise reported a similar trend for tenera palm kernel. No significant differences between sphericity mean values were observed at p ≤ 0.05 for all moisture levels and confirmed by ANOVA results with p ‐value > 0.05 (Tables 2 and 4).…”
Section: Resultsmentioning
confidence: 61%
“…The highest value of 0.605% at 32.5% (db) mc presents that the seed is oval. Habibiasr et al (2020) likewise reported a similar trend for tenera palm kernel. No significant differences between sphericity mean values were observed at p ≤ 0.05 for all moisture levels and confirmed by ANOVA results with p ‐value > 0.05 (Tables 2 and 4).…”
Section: Resultsmentioning
confidence: 61%
“…Indeed, this decrease can be caused by the increase in the heat of absorption in the case of high temperatures, which makes it possible to reduce the EMC [32,33]. Benseddik et al and Ferradji and Matallah [26,34] isotherms with an increase in temperature is relative to the composition of the products in starch content and its solubility with an increase in thermal agitation within the samples [35]. Though, at high temperatures, the state of excitation is stronger and favors the reduction of the forces of attraction of molecules among them (Figure 3).…”
Section: Models Equationsmentioning
confidence: 99%
“…Palm kernel oil has a similar composition to coconut oil, and both oils are key suppliers of lauric oil on the global market 1 . On a dry basis, palm kernel oil comprises 0.5 kg oil kg −1 , 2 which is used in the food, pharmaceutical and chemical sectors. The goal of drying palm kernels is to reduce the moisture content to around 0.07 kg moisture kg −1 (dry basis) to be appropriately kept and transported without deterioration 3 .…”
Section: Introductionmentioning
confidence: 99%